2001
DOI: 10.1021/bi010580s
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activity of the NPR-A Kinase Triggers Dephosphorylation and Homologous Desensitization of the Receptor

Abstract: NPR-A, the receptor for the atrial natriuretic peptide (ANP), is a 130-kDa protein presenting an extracellular ANP-binding domain, a single transmembrane domain, an intracellular regulatory kinase homology domain (KHD), and a guanylyl cyclase catalytic domain. Upon stimulation, NPR-A receptors are activated to produce cyclic guanosine monophosphate (cGMP) and are subsequently desensitized through dephosphorylation of residues at their KHD. We used wild-type rat (r) NPR-A (WT) and a disulfide-bridged mutant (C4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 58 publications
1
35
2
Order By: Relevance
“…Recently, Joubert et al (28) reported that ANP-dependent dephosphorylation of NPR-A in whole transfected 293 cells results primarily from the inactivation of the NPR-A kinase, with little contribution from increased phosphatase activity. These data are completely consistent with our findings in the 293-NPR-A model system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Joubert et al (28) reported that ANP-dependent dephosphorylation of NPR-A in whole transfected 293 cells results primarily from the inactivation of the NPR-A kinase, with little contribution from increased phosphatase activity. These data are completely consistent with our findings in the 293-NPR-A model system.…”
Section: Discussionmentioning
confidence: 99%
“…This process is called homologous desensitization and is mediated, at least in part, by dephosphorylation of all six NPR-A phosphorylation sites, a process termed global dephosphorylation (27)(28)(29)(30). Consistent with this model of desensitization, a "constitutively phosphorylated" version of NPR-A containing glutamate residues at all six phosphorylation sites (NPR-A-6E) to mimic the negative charge of phosphate is hormonally responsive and resistant to homologous desensitization (31).…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…ATP increases the activity of both receptors in broken cell preparations by serving as a phosphate donor (11)(12)(13). ATP is also an allosteric activator that reduces the Michaelis-Menten constant without affecting maximal velocities (14).…”
Section: Natriuretic Peptides and Atp Activate And Gö6976 Inhibits Gumentioning
confidence: 99%
“…Each receptor consists of an extracellular ligand-binding domain, single membrane-spanning domain, and an intracellular region made up of a kinase homology domain-regulatory, hinge-dimerization, and guanylyl cyclase-catalytic domains. Phosphorylation of the kinase homology domains of NPR-A and NPR-B is required for natriuretic peptide-dependent activation (30), and receptor dephosphorylation is associated with desensitization (21,22,30,32,33). Although all particulate guanylyl cyclases contain a domain with limited homology to protein kinases, only GC-E has been reported to possess intrinsic phosphotransferase activity (4).…”
mentioning
confidence: 99%